2018
DOI: 10.1007/s10964-018-0933-3
|View full text |Cite
|
Sign up to set email alerts
|

Persistence Mindset among Adolescents: Who Benefits from the Message that Academic Struggles are Normal and Temporary?

Abstract: Research proposing that mindset interventions promote student achievement has been conducted at a frenetic pace nationwide in the United States with many studies yielding mixed results. The present study explores the hypothesis that mindset interventions are beneficial for students only under specific circumstances. Using a randomized controlled trial with student-level random assignment within two public schools (School 1: n = 198 seventh-graders, 73% Black, 27% White, 53% male; School 2: n = 400 ninth-grader… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 60 publications
1
38
0
Order By: Relevance
“…A similar finding was uncovered by Binning et al. (), who found that White adolescent students who reported high academic expectations at the beginning of the academic year actually had lower year‐end GPAs if they were exposed to a mindset intervention than if they were assigned to a control condition consisting of mathematics practice.…”
Section: Unpacking the Five Zones Of Threatsupporting
confidence: 75%
See 1 more Smart Citation
“…A similar finding was uncovered by Binning et al. (), who found that White adolescent students who reported high academic expectations at the beginning of the academic year actually had lower year‐end GPAs if they were exposed to a mindset intervention than if they were assigned to a control condition consisting of mathematics practice.…”
Section: Unpacking the Five Zones Of Threatsupporting
confidence: 75%
“…In one set of studies, African American seventh graders who completed a series of in‐class self‐affirmation writing exercises showed benefits on their academic performance that persisted 7–9 years later (e.g., greater college attendance; Goyer et al., ). Several other studies have shown that social–psychological interventions can bolster student outcomes (e.g., higher grade point averages [GPAs], fewer discipline incidents) for multiple years after the initial intervention (e.g., Binning, Wang, & Amemiya, ; Borman, Grigg, Rozek, Hanselman, & Dewey, ; Tibbetts et al., ; Yeager et al., ).…”
mentioning
confidence: 99%
“…Nonetheless, confirmed strength in ethnic‐racial socialization's link with academic motivation is remarkable. Not only is there a wealth of evidence showing motivation's direct relationship with grades and school performance, but positive motivational beliefs are also linked to greater psychological well‐being (Binning, Wang, & Amemiya, ; Deci & Ryan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also demonstrate that students in the lower academic track adhere to a fixed mindset about SRL and possess lower strategy knowledge than their peers in the higher academic track do. Interventions that focus on mindsets have proven to be particularly relevant for low-performing and disadvantaged students and represent an important contribution to increasing equality and educational opportunities for those students (Binning et al, 2019). Therefore, low-performing students could especially benefit from combined training that focuses on mindsets about SRL and SRL.…”
Section: Practical Implicationsmentioning
confidence: 99%